THE ROLE OF INTERDISCIPLINARY COMMUNICATION IN TEACHING PHYSICS (American Journal of Technology and Applied Sciences, 2023)
This article will talk about the important role of interdisciplinary communication in teaching physics. Physics, a multidisciplinary specialty, requires effective communication between different disciplines to increase students ' understanding and appreciation of its concepts. Raising the gap between physics and other sciences, interdisciplinary dialogue illuminates real-world programs and shapes critical thinking, problem-solving skills, collaboration, and teamwork. This article highlights the importance of integrating interdisciplinary approaches in physics education to give students a holistic understanding and prepare them for the complexities of the scientific challenges they may face in their future endeavors.